PERANAN MAHASISWA FAKULTAS HUKUM SEBAGAI PELAKSANA BANTUAN HUKUM (LEGAL AID) KEPADA MASYARAKAT - Achmad, Deni (FIAT JUSTISIA, 2015)
The role of law students in the implementation of legal aid is divided into two, namely the implementation of legal aid litigation and non-litigation legal aid. The role of students in the provision of legal aid services, urgent existence, considering many people who are not capable of, marginalized and legally blind in Indonesia is difficult to get access to justice, especially a dense population and spread across a wide area so it is not proportional to the number Advocates are available and include high student awareness of the legal issues faced by the community/communities are not able to. Students have contributed significantly in their communities by providing legal aid services, running the advocacy work and organizing in their communities in order to encourage growth is growing awareness of the laws of society and realize access to justice (acces to justice) for everyone, especially people not being able to obtain a guarantee in the fulfillment of their rights as citizens, especially equality before the law (equality before the law) as mandated by the constitution in Article 28D paragraph (1) and Article 28H paragraph (2) of the constitution of 1945 .Keywords: Student, Legal Aid, Role